Predicting gas evolution during steam gasification of chars derived from biomass pyrolysis - Rivas-Márquez, M.N.; Ruiz-Rosas, Ramiro Rafael; Rosas-Martínez, Juana María; Rodríguez-Mirasol, José; Cordero-Alcántara, Tomás (Elsevier, 2026)
A kinetic study of the steam gasification process of biomass chars has been developed. Chars were prepared from hemp stem, almond shell, and olive stone by slow pyrolysis at 800 °C. Subsequently, these samples were gasified with water vapor (30 % (v/v) in N2) in a temperature range of 800 – 900 °C. A modified random pore model considering nascent catalyst site, better predicted the experimental conversion data, showing activation energies of 120 – 180 kJ/mol. A surface reaction mechanism was developed to predict the evolution of H2, CO and CO2, which was modified to include the evolution of the porous structure during gasification using random pore model and the catalytic effect of the inorganic matter present in the chars. This model represents a novel contribution by explicitly integrating these aspects into a single kinetic expression, providing a valuable tool for the comprehensive analysis of the gasification process. The profiles of the gases and the conversion curves are successfully predicted over the whole temperature range with the model combining both modifications, giving values of the kinetic constants that follow the pattern of the inorganic matter content.
Keywords: Gases; Steam gasification; Reactivity; Catalytic gasification; Kinetic study; Gases prediction